A STUDY ON THE CONFLICTING IDEAS OF BLACK WOMEN’S ROLES IN SULA AND NEL’S FRIENDSHIP AS SEEN IN TONI MORRISON’S SULA - Hendaria Kamandhari, Helen (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Toni Morrison’s Sula portrays the conflicting ideas of two black women, Sula and Nel who used to settle themselves as soulmates. Starting as friends of deepest emotion and sharing all the deepest dark secrets in Medallion, Sula and Nel continue their journeys of life in separation and come to the gate of adulthood which drags them to meet again in different encounter. Those years of separation between both of them have set enough barriers on their relationship to know each other better as they used to in the past. Sula’s and Nel’s teenagehood which has been spent on different places brought them into an unending conflict of black women’s roles in their relationships as friends.